Relationship between hemoglobinopathies and male infertility: a scoping review - Abdullah M. Al-Jubouri (22155823) (2024)
Infertility is a common issue that threatens couples worldwide. Infertility can result from the male or female partner alone, or both partners. It can be due to multiple factors related to the patient’s overall health or lifestyle. Causes related to patient health can be systemic or related to gonadal dysfunction. One of the systematic causes can be hematological. The two most common hemoglobinopathies that are thought to cause infertility, especially male infertility, are sickle cell disease (SCD) and thalassemia major (TM). These two hemoglobinopathies cause male infertility through pathophysiological alterations. Specifically, they alter the oxygen carrying ability of red blood cells (RBCs), causing tissue hypoxia that affects the normal physiological process of spermatogenesis, eventually inducing infertility. Semen analyses and other systemic blood testing can be used to investigate male infertility. Both hemoglobinopathies can be helped by blood transfusions, which can then alleviate male infertility. This paper aims to explore the relationship between hemoglobinopathies (SCD and TM) and their role in contributing to male infertility, in addition to the role of blood transfusions in addressing male infertility by correcting the root cause. Other Information Published in: International Journal of Hematology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12185-024-03844-7